2005
DOI: 10.1017/s0140525x05320097
|View full text |Cite
|
Sign up to set email alerts
|

what's in a heuristic?

Abstract: With respect to questions of fact, people use heuristics -mental short-cuts, or rules of thumb, that generally work well, but that also lead to systematic errors. People use moral heuristics too -moral short-cuts, or rules of thumb, that lead to mistaken and even absurd moral judgments. These judgments are highly relevant not only to morality, but to law and politics as well. Examples are given from a number of domains, including risk regulation, punishment, reproduction and sexuality, and the act/omission dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…This suggests the possible use of heuristics (see Newell & Simon, 1972;Tversky & Kahneman, 1974) in value-based decisions. Relevant to this hypothesis, several authors have previously sought to make a case for moral heuristics (e.g., Baron, 1993;Sunstein, 2005; see also Hahn, Frost, & Maio, 2005), such as the distinction that is made between acts of omission and acts of commission. Baron and colleagues (e.g., Haidt & Baron, 1996;Spranca, Minsk, & Baron, 1991) found that participants judge individuals more harshly for an act of commission than for an act of omission, even given the involvement of the same principles.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the possible use of heuristics (see Newell & Simon, 1972;Tversky & Kahneman, 1974) in value-based decisions. Relevant to this hypothesis, several authors have previously sought to make a case for moral heuristics (e.g., Baron, 1993;Sunstein, 2005; see also Hahn, Frost, & Maio, 2005), such as the distinction that is made between acts of omission and acts of commission. Baron and colleagues (e.g., Haidt & Baron, 1996;Spranca, Minsk, & Baron, 1991) found that participants judge individuals more harshly for an act of commission than for an act of omission, even given the involvement of the same principles.…”
Section: Discussionmentioning
confidence: 99%
“…Moral heuristics, as defined by Cosmides and Tooby [20] , are "decision rules that generate intuitions about fairness and justice, punitiveness and approval, right and wrong." Examples include principles like 'always keep your promise' [21] and 'it is wrong to hurt some people for the benefit of others' [22] . Although the exploration of moral judgment traces back to Dewey [23] , a significant portion of the literature stems from articles published in 2005 in the journal 'Behavioral and Brain Sciences'.…”
Section: Moral Heuristicsmentioning
confidence: 99%